Double-Opposing Z-Plasty for Secondary Surgical Management of Velopharyngeal Insufficiency Following Primary Furlow Palatoplasty. (May 2018) - Gosain, Arun K.; Chim, Harvey; Sweeney, Walter M.
Objective: The present study investigates the efficacy of performing a "palate rerepair" utilizing a double-opposing z-palatoplasty (DOZ) following primary Furlow palatoplasty. Design: Retrospective study. Setting: Tertiary referral academic center for craniofacial surgery. Patients: 15 consecutive patients who presented with velopharyngeal insufficiency (VPI) after primary Furlow palatoplasty. Main Outcome Measures: All subjects were evaluated using the perceptual speech assessment (PSA) scale. Criteria for inclusion in the study were (1) velopharyngeal gap size on phonation of 7 mm or less and (2) lateral wall motion at least 40% normal. Results: Mean PSA score was 7.13 + 3.31 (range 3-13) preoperatively, and decreased to 1.80 + 2.83 (range 0-11; P < .001 vs baseline) 3 months or more after surgery. A sphincter pharyngoplasty was performed as a tertiary procedure in 2 patients due to persistent nasal air emission. There was no symptomatic airway compromise following secondary or tertiary management in all patients. Presence of a cleft lip, lateral wall motion, and velopharyngeal gap size did not impact outcomes. Conclusions: We have demonstrated that a DOZ performed secondarily is anatomically possible following Furlow palatoplasty and can restore function of the levator muscle despite significant scarring following primary repair. This approach respects anatomic principles of palatoplasty without eliminating the possibility for extrapalatal procedures should velopharyngeal competence not be achieved.